Ex-ante evaluation of economic impacts of adopting improved forages in the Colombian Orinoquía - Enciso, Karen; Charry, Andrés; Rincón Castillo, Álvaro; Burkart, Stefan (Frontiers Media, 2021)
Forage-based cattle systems play a key role in rural economies of developing countries in terms of food security and poverty alleviation. However, they can generate negative environmental impacts by contributing to increased greenhouse gas emissions, land degradation, and reduction of biodiversity. As a result of that, large amounts of resources have been allocated to research and development (R&D) in forage material improvement and a broad range of improved materials were released showing superior characteristics in terms of productivity and environmental impacts compared to native or naturalized materials. However, data are still scarce on both the economic and environmental “yields” of investments in R&D activities around improved forage materials. Through an ex-ante evaluation, this study aims at estimating the potential “yields” of the investment in R&D and diffusion activities of the improved forage variety Brachiaria brizantha 26,124 cv. Agrosavia Caporal in the Colombian Orinoquía region. The analysis used two evaluation methodologies: 1) a combined discounted free cash flow model and Monte Carlo simulation using the simulation software @Risk to determine the impact on individual welfare, and 2) an economic surplus model an risk analysis to determine the potential social benefits of the technologies and their distribution among producers and consumers, considering changes in adoption rates, productivity levels and probability of success. The results suggest that the evaluated material presents important economic benefits for the study region and results in a positive return on the investments made in R&D activities. The results are a key input for decision making processes among public and private institutions involved in funding and executing the development of improved forage materials and will help to set research priorities and resource allocation.